Representasi Prestasi Atlet Maraton dalam Unggahan Instagram @adidasrunning Bertajuk “History in Time” - Haidar Nugroho Dwifandi; Rahardian Shandy Ekohandito (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Maintaining a strong identity is essential for a brand like Adidas to ensure consistency in its marketing communication strategy, especially on social media. Through its Instagram account, @adidasrunning, Adidas aims to uphold its identity by creating meaning through narratives and visual representations featured in its marketing campaigns. One of the campaigns is titled "History in Time." This study aims to analyze the representations used by Adidas in the Instagram post from @adidasrunning called "History in Time" and to uncover the meanings constructed within it. The research employs a qualitative descriptive method using a semiotic approach. Data were collected through observation, documentation, and a literature review. The analysis is based on Roland Barthes' semiotic framework, which highlights three levels of meaning: denotation, connotation, and myth. The findings reveal that athletes’ achievements are represented through images of victory, emotional expressions, and the integration of Adidas products, generating meanings associated with hard work, dedication, and accomplishment. At the mythological level, athletes are constructed as symbols of innovation, high performance, and history-making achievement. Consequently, athletic success is portrayed not only as an individual accomplishment but also as a representation of Adidas’ brand identity. These findings demonstrate that Instagram serves as an effective visual communication medium for strengthening brand image through the representation of athletic achievement.